Oxide/hydroxide films on tin. Part I: Kinetic aspects of the electroformation and electroreduction of the films - Brunetti, Veronica (2008)
The anodic behaviour of tin in borate solutions has been studied by linear potential sweep voltammetry and triangularly modulated triangular potential sweeps. It is shown that the active to passive transition involves the formation of intermediate soluble species followed by the precipitation of a tin oxide/hydroxide layer that passivates the electrode. The potentiodynamic current-potential behaviour is adequately described by using the Layer-pore-resistance model. A good agreement between experimental and theoretical curves is obtained which allow us to demonstrate that primary passivation of tin in alkaline borate solutions (pH 8.9) as well as the film electroreduction is mainly controlled by the resistance of the electrolyte in the pores of the layer. In addition, the triangularly modulated triangular potential sweep method is applied in order to analyze the existence of reaction intermediates.Layer-pore-resistance model. A good agreement between experimental and theoretical curves is obtained which allow us to demonstrate that primary passivation of tin in alkaline borate solutions (pH 8.9) as well as the film electroreduction is mainly controlled by the resistance of the electrolyte in the pores of the layer. In addition, the triangularly modulated triangular potential sweep method is applied in order to analyze the existence of reaction intermediates.